1994
DOI: 10.2307/3579122
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Aberrations after Treatment with Radioactive Iodine for Thyroid Cancer

Abstract: The study aimed to investigate whether the determination of chromosome aberrations in circulating blood lymphocytes could be useful to assess whole-body exposure from radioactive iodine released accidentally. Ten patients treated with two doses of 1850 MBq of 131I given 24 h apart for thyroid cancer were studied for chromosome aberrations (dicentrics) in blood samples taken before and at various times after exposure. The increase in the yield of aberrations caused by the exposure to iodine was small but statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…Therefore, it is important to allow for recovery of bone marrow between 131 I treatments. In support of these clinical observations, 131 I has been shown in peripheral lymphocytes to induce a significant increase in the number of dicentric chromosomes (275)(276)(277), and the aberrations of chromosomes 1, 4, and 10 are not only more prevalent but are still apparent after 4 years (276). A recent report comparing thyroid hormone withdrawal to rhTSH suggests a lower frequency of lymphocyte chromosomal rearrangements after 131 I dosing using rhTSH preparation (278).…”
Section: Recommendation Rating: Bmentioning
confidence: 75%
“…Therefore, it is important to allow for recovery of bone marrow between 131 I treatments. In support of these clinical observations, 131 I has been shown in peripheral lymphocytes to induce a significant increase in the number of dicentric chromosomes (275)(276)(277), and the aberrations of chromosomes 1, 4, and 10 are not only more prevalent but are still apparent after 4 years (276). A recent report comparing thyroid hormone withdrawal to rhTSH suggests a lower frequency of lymphocyte chromosomal rearrangements after 131 I dosing using rhTSH preparation (278).…”
Section: Recommendation Rating: Bmentioning
confidence: 75%
“…Watanabe et al [10] reported that the incidence of micronuclei has been elevated as a consequence of 131 I exposure. Baugnet-Mahieu et al [8] reported a small but significant increase in chromosomal aberration in the lymphocytes of patients with thyroid cancer treated with 1850 MBq of 131 I for 24 h.…”
Section: Discussionmentioning
confidence: 98%
“…It has earlier been shown that 99m Tc-MIBI is particularly accumulated in peripheral blood lymphocytes, which are recognized to be extremely vulnerable to radiopharmaceuticals [7]. There are also reports in which 131 I has resulted in increased micronuclei incidence in peripheral lymphocytes [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…So far, there have been many studies on the biological damages after radioiodine treatment, however, there are very few reports regarding the effects of radiation emitted by radioactive iodine on the immune system (Baugnet-Mahieu et al, 1994).…”
Section: Introductionmentioning
confidence: 99%